Analyzing Panic Buying Behavior In An Era Of Uncertainty: The Role Of Fear Of Missing Out (FOMO) And Social Influence As Mediating Variables - Yoyo Indah Gunawan; Aloysius Gonzage Eka Wenats Wuryanta; Dian Firdaus; Hadiansyah Ma’sum; I Gusti Made Riko Hendrajana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The phenomenon of panic buying has become a global concern with the increasing frequency of crises, ranging from pandemics and geopolitical instability to natural disasters. This study aims to analyze panic buying behavior in an era of uncertainty by focusing on the role of Fear of Missing Out (FOMO) and social influence as mediating variables. Using a quantitative approach with a survey of consumers who have made emergency purchases, the data were analyzed using Structural Equation Modeling (SEM). The results show that the perception of uncertainty significantly triggers psychological anxiety, which then manifests in the form of FOMO and susceptibility to social pressure. Both variables are proven to mediate the relationship between environmental uncertainty and consumers' decisions to hoard goods. These findings confirm that panic buying is not simply a logistical response to scarcity, but rather a manifestation of emotional contagion and maladaptive coping strategies. The practical implications of this study urge governments and retailers to manage information narratives to minimize the effects of FOMO during periods of crisis.